Walking, Explore Race and Flying Fox Adventure Activity in Learning Statistics: Effect on Leadership Skills - Mohd Afifi Bahuruddin; Nor'ain Mohd Tajudin; Mazlini Adnan (Didaktik Matematika, 2016)
The unemployment issue has opened the eyes of academic scientists and government. These things give the impression that the teaching and learning needs to be improved. One of the strategies that have been suggested by the Malaysia Education Blueprint (Higher Education) is to use experience-based approach. Teaching methods and adventure-based learning is a method characterized by experiential learning and inquiry learning. It is seen as having the characteristics of improving the skills of the 21st century in terms of leadership. The main objective of this study was to examine the effects of adventure-based learning through walks, explore race and flying fox in learning statistics (mathematics) against the student leadership skills. This study will employ a quantitative approach research using a quasi-experimental pre and post-test non-equivalent control group design. The sample for this study will be selected randomly at one Malaysia Teacher Training Institute and will be involved semester two students in Program Persediaan Ijazah Sarjana Muda Perguruan. Three main instruments will be used in this study such as the fundamental statistic achievement test, critical thinking test and leadership assessment questionnaire. The sample will be divided into two groups: the experimental groups will undergo an adventure-based learning approach while control groups remain to the conventional approach. The results of this study are expected to provide an alternative teaching approach that can be implemented by lecturers, teachers and educators in practicing the teaching and learning for the 21st century.